Analytical review on information retrieval methods and applications in the Semantic Web - Grishanova, I.J. (PROBLEMS IN PROGRAMMING, 2018)
The article describes and analyzes the Information Retrieval (IR) methods and applications in the environment of Semantic Web. The author provided the basic Information Retrieval concepts, problems, models and classification of IR systems on various grounds. Examples of existing modern search engines, as well as highlighted the stages of development and listed a list of functional and architectural features of 3-rd search engines generation. The proposed model of IR extends the classification of search engines and search model with the possibility of finding new objects that have become available in the web, and use knowledge represented in the Semantic Web.Prombles in programming 2016; 1: 51-72